Website-Based Local Wisdom Learning Media of Bali to Enhance Student Learning Interest in the Subject of IPAS on Photosynthesis - Anak Agung Ayu Mirah Widiantari; I Gede Margunayasa; Kadek Edi Yudiana (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the low academic performance of students, which was caused by teacher-centered learning, insufficient learning media, and low student interest in learning. To address these issues, learning should be connected to relevant and engaging concepts to help students better understand the material and stay focused in class. Consequently, a website-based learning media incorporating Balinese local wisdom was developed for the science subject (IPAS) on the topic of photosynthesis for fourth-grade elementary school students. The study employed the ADDIE model approach (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of 20 students, while the object of the study was the website-based learning media incorporating Balinese local wisdom. The data analysis techniques used were descriptive quantitative and descriptive qualitative methods. Data were collected using questionnaires, and the study utilized a pre-experimental design with a one-group pretest-posttest method. The results of this study indicated that the website-based learning media incorporating Balinese local wisdom for the science subject on photosynthesis was categorized as